2022
DOI: 10.3201/eid2813.220728
|View full text |Cite
|
Sign up to set email alerts
|

A Nationally Representative Survey of COVID-19 in Pakistan, 2021–2022

Abstract: We conducted 4,863 mobile phone and 1,715 face-to-face interviews of adults > 18 years residing in Pakistan during June 2021–January 2022 that focused on opinions and practices related to COVID-19. Of those surveyed, 26.3% thought COVID-19 was inevitable, and 16.8% had tested for COVID-19. Survey participants who considered COVID-19 an inevitability shared such traits as urban residency, concerns about COVID-19, and belief that the virus is a serious medical threat. Survey respondents wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…However, overall, in all three waves, only 18.8% (less than one-third) of the participants reported COVID-19 testing with 51.3% (almost half) reporting to have had FLS as well and 35.6% (slightly over one-third) also reported being exposed to FLS by their families (Table 4 ). The testing rate in this study is quite similar to another study conducted in Pakistan which reported a testing rate of 16.8% [ 13 ]. This strongly suggests that the overall testing trend remained low despite high rates of symptoms and exposure which strongly suggests under-reporting of the COVID-19 cases in Pakistan.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, overall, in all three waves, only 18.8% (less than one-third) of the participants reported COVID-19 testing with 51.3% (almost half) reporting to have had FLS as well and 35.6% (slightly over one-third) also reported being exposed to FLS by their families (Table 4 ). The testing rate in this study is quite similar to another study conducted in Pakistan which reported a testing rate of 16.8% [ 13 ]. This strongly suggests that the overall testing trend remained low despite high rates of symptoms and exposure which strongly suggests under-reporting of the COVID-19 cases in Pakistan.…”
Section: Discussionsupporting
confidence: 88%
“…Despite being the world's fifth-most-populous country, Pakistan has recorded the world's 29th-highest death toll (at approximately 23,087) and 29th-highest number of confirmed cases (at approximately 1,011,708 much lower than its neighbors India and Iran till 2021) [ 11 , 12 ]. Pakistan was the first country to suggest and implement a smart lockdown strategy to combat one of the worst pandemics in history [ 13 ]. On the contrary, unfortunately, Pakistan also ranks 103rd out of 132 countries in testing capacity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEPFAR-supported HIV and TB information management systems and diagnostic networks were adapted for SARS-CoV-2 testing in 16 low- to middle-income countries during the pandemic ( 7 ). Surveys provided key data on SARS-CoV-2 cases in Pakistan ( 8 ) and Malawi ( 9 ). Ohlsen et al found international disparities in SARS-CoV-2 sequencing capacity and timeliness while viral genomic surveillance coverage increased globally ( 10 ).…”
Section: Surveillance Information and Laboratory Systemsmentioning
confidence: 99%
“…On February 26, 2020, Pakistan reported its inaugural COVID-19 case, prompting an immediate outbreak declaration. By December 31, 2021, Pakistan had documented over 1,290,000 confirmed cases and 28,909 COVID-19-related deaths [ 2 ]. The initial fatality was recorded on March 18, 2020, in Mardan, KP, Pakistan, sparking increased chaos and fear within the population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%